Marangoni flow traveling with reaction fronts: Eikonal approximation - Guzman, R (2017)
This work was supported by CONCYTEC (Convention No. 026-2015-FONDECYT). This work was also supported by a grant from the Dirección de Gestión de la Investigación (DGI 2016-3-0025) of the Pontificia Universidad Católica del Perú.